2011
DOI: 10.1080/13854046.2011.565075
|View full text |Cite
|
Sign up to set email alerts
|

Visual Acuity Is Associated with Performance on Visual and Non-Visual Neuropsychological Tests in Multiple Sclerosis

Abstract: Both vision and cognitive problems are commonplace in multiple sclerosis. Previous research suggests that MS patients with compromised near vision perform more poorly on visually mediated cognitive tests. Consequently it has been recommended that neuropsychologists who evaluate MS patients with poor corrected near vision should rely primarily on auditory neuropsychological tests. However, no research has examined the association between vision problems and performance on non-visual neuropsychological tests in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
9
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 34 publications
1
9
0
Order By: Relevance
“…These findings may be in accordance with prior studies, which suggest that not only may LCLA better capture visual dysfunction in MS than HCVA, but also that LCLA may be a more encompassing and reliable biomarker and outcome reflective of the MS disease process [28]. Additionally, our study findings support preliminary studies that found associations between LCLA and cognitive function in a small sample of RRMS and SPMS patients [11], and decreased visual-cognitive performance in MS measured by the King-Devick test [29]. Importantly, similar relationships within the visual-cognition axis have been implicated in other neurological disorders, including Alzheimer’s disease [30] and Parkinson’s disease [31].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings may be in accordance with prior studies, which suggest that not only may LCLA better capture visual dysfunction in MS than HCVA, but also that LCLA may be a more encompassing and reliable biomarker and outcome reflective of the MS disease process [28]. Additionally, our study findings support preliminary studies that found associations between LCLA and cognitive function in a small sample of RRMS and SPMS patients [11], and decreased visual-cognitive performance in MS measured by the King-Devick test [29]. Importantly, similar relationships within the visual-cognition axis have been implicated in other neurological disorders, including Alzheimer’s disease [30] and Parkinson’s disease [31].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, there have been conflicting results between studies performed. Peripapillary retinal nerve fiber layer (RNFL) thickness has been found to correlate with SDMT scores in some studies [8-10], and low-contrast letter acuity has been found to be associated with PASAT and SDMT scores [11,12]. However, with relatively small sample sizes, limited neuropsychological evaluation, and partial VP assessment (GCIP thickness, for example, has been shown to be a more superior OCT measure than RNFL thickness as it more greatly reflects global neurodegeneration in MS and is less susceptible to edema [1]), the relationships between VP measures and neuropsychological function in MS remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…A recent study investigating auditory-based cognitive tests (i.e. PASAT) in combination with low contrast visual acuity showed that the latter correlates strongly with visually dependent but also non-visually dependent cognitive test results [37]. However, crucially, the authors did not compare their findings to actual damage to the visual pathway [13].…”
Section: Discussionmentioning
confidence: 99%
“…The classic cortical response in visual evoked potential (VEP) measures is delayed latency with normal amplitude. Baier et al 28 X X X X X Balcer et al 13 X X X X Balcer et al 94 X X Bock 97 X X Burkholder et al 69 X X Chahin et al 53 X X X X Davies et al 71 X X Feaster 98 X X Fisher et al 20 X X Frohman et al 73 X X X Frohman 99 X X Galetta et al 62 X X Garcia-Martin 100 X X Graves 101 X X Henderson et al 60 X X Maghzi et al 74 X X X Mowry et al 87 X X X Noble et al 88 X X Oh 102 X X X Pineles et al 33 X X X Pulicken et al 63 X X Rasova 103 X X X Reich et al 24 X X X Sabadia et al 90 X X X Saidha et al 64 X X X Salter et al 81 X Schinzel et al 54 X X X X X X Schnurman et al 80 X X Seigo et al 70 X X X Shandiz et al 79 X X Smith et al 75 X X X Talman et al 21 X X Waldman et al 61 X X Walter et al 22 X X X Weinstock-Guttman et al 78 However, when anterior visual pathway axonal loss is present (often manifested by OCT RNFL and GCL + IPL thinning), amplitude is also decreased. 76 Lowcontrast VEPs may be used to measure contrast sensitivity in MS, 16 typically demonstrating increased latencies or absent waveforms compared to VEPs with high-contrast stimuli.…”
Section: Criterion Validity: Structural and Electrophysicologic Correlationmentioning
confidence: 99%